An Analysis Meanings of Hapo Ana (Thanksgiving for the Birth of a Child) Ritual Speech in Raerobo Communities of Sabu Raijua Regency: English - Rohi, Trivos Ariance; Isu, Rudolof; Dewi, Ni Putu Juliani L. (Universitas Persatuan Guru 1945 NTT, 2024)
The purpose of this study was to describe the meaning contained in the Hapo Ana (thanksgiving for the birth a child) Ritual Speech in the community of Raerobo Village, Sabu Liae Subdistrict, Sabu Raijua District. The problem raised in this research is what are the meanings contained in the Hapo Ana (thanksgiving for the birth a child) Ritual Speech in the Raerobo Village community, Sabu Liae Subdistrict, Sabu Raijua District. The theory used in this research is the theory of hermeneutics. The method used by the author in assessing the meaning in the ritual speech